Transmural impedance detects graded changes of inflammation in experimental colitis. Issue 2 (19th February 2020) - Payne, Sophie C.; Alexandrovics, Jack; Thomas, Ross; Shepherd, Robert K.; Furness, John B.; Fallon, James B.
Abstract : Ulcerative colitis is a chronic disease in which the mucosa of the colon or rectum becomes inflamed. An objective biomarker of inflammation will provide quantitative measures to support qualitative assessment during an endoscopic examination. Previous studies show that transmural electrical impedance is a quantifiable biomarker of inflammation. Here, we hypothesize that impedance detects spatially restricted areas of inflammation, thereby allowing the distinction between regions that differ in their severity of inflammation. A platinum ball electrode was placed into minimally inflamed (i.e. normal) or 2, 4, 6-trinitrobenzene sulphonic acid (TNBS)-inflamed colonic regions of rats and impedance measurements obtained by passing current between the intraluminal and subcutaneous return electrode. Histology of the colon was correlated with impedance measurements. The impedance of minimally inflamed (normal) tissue was 1.5–1.9 kΩ. Following TNBS injection, impedance significantly decreased within the inflammatory penumbra ( p < 0.05), and decreased more in the inflammatory epicentre ( p = 0.02). Histological damage correlated with impedance values ( p < 0.05). Thus, impedance values of 1.5–1.9, 1.3–1.4 and 0.9–1.1 kΩ corresponded to minimally inflamed, mildly inflamed and moderately inflamed tissue, respectively. In conclusion, transmural impedance is an objective, spatially localized biomarker of mucosal integrity, and distinguishes between severities of intestinal inflammation.